2015
DOI: 10.5114/ceji.2015.54596
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in the blood and semen of infertile patients

Abstract: Cytokines have been important mediators of the immunity and can be involved in numerous processes in the male genital tract including acting as immunomodulatory elements within the male gonad.The aims of this study were: 1) to detect pro- and anti-inflammatory cytokine levels in the control group and subgroups of infertile men; and 2) to set up the practical recommendations concerning determination of cytokine levels for the male infertility diagnosis.Observations were performed in a group of 82 men: healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 43 publications
2
49
0
13
Order By: Relevance
“…Supporting this finding, it has been found that GSH levels, the activities of GR and GPx, were decreased in infertile men compared with the control group . Moreover, N‐nitrosamines caused severe inflammations and consequently increased the levels of cytokines, tumor necrosis factor‐alpha (TNF‐α), interleukin‐1 alpha (IL‐1 α) and interleukin 1 beta (IL‐1 β) cytokines in the male reproductive tract (testis, epididymis and sperm) . Also, Chlamydia positive women with tubal infertility have higher IL‐10 than controls, which may contribute to their development of tubal pathology .…”
Section: Discussionmentioning
confidence: 85%
“…Supporting this finding, it has been found that GSH levels, the activities of GR and GPx, were decreased in infertile men compared with the control group . Moreover, N‐nitrosamines caused severe inflammations and consequently increased the levels of cytokines, tumor necrosis factor‐alpha (TNF‐α), interleukin‐1 alpha (IL‐1 α) and interleukin 1 beta (IL‐1 β) cytokines in the male reproductive tract (testis, epididymis and sperm) . Also, Chlamydia positive women with tubal infertility have higher IL‐10 than controls, which may contribute to their development of tubal pathology .…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, leucocytospermia is associated with high reactive oxygen species (Henkel et al, 2003) and also with high cytokine production. Cytokines have been regarded as crucial players of the immune system and can be involved in various processes in the male genital tract including acting as immunomodulatory factors within the male gonad (Haidl, Haidl, Allam, & Schuppe, 2019;Havrylyuk et al, 2015). It is important to note that cytokines mostly act together in a network, which in turn can impair spermatogenesis directly or even indirectly (Seshadri et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Besides several discussed factors playing a role in fertility dysfunction of men, IL-6 with its receptor can be regarded as useful biomarkers for genital tract inflammation leading to subfertility. Furuya, Akashi, & Fuse, 2003;Havrylyuk et al, 2015). Moreover, to integrate IL-6 as an possibly important biomarker parameter for genitourinary tract inflammation (Haidl, Haidl, Oltermann, & Allam, 2015) in the routine sperm analysis could be one crucial step for analysing one cause of subfertility, because the role and function of leucocytes in semen, as well as their clinically relevant pathological threshold values, are a matter of debate (Havrylyuk et al, 2015;Lotti et al, 2011).…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Человеческая семенная жидкость содержит богатый набор цитокинов, хемокинов и других сигнальных факторов клетка-клетка, способных действовать как сигнальные агенты в тканях женского репродуктивного тракта. Среди них три изоформы трансформирующего фактора роста-β (TGF-β), интерлейкины IL-1A, IL-1B, IL-2, IL-7, IL-10, IL-17, IL-8 (хемокин CXCL8), гранулоцитарный макрофагальный колониестимулирующий фактор GM-CSF (CSF2), фактор некроза опухоли (TNF-α), фактор роста эндотелия сосудов (VEGF), а также простагландины (PGE) и стероидные гормоны [8][9][10][11][12][13]. Эти биологически активные вещества могут играть роль в формировании посткоитального воспалительного ответа в половых путях женщины [14].…”
unclassified